2016
DOI: 10.3109/10409238.2016.1172552
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and regulation of DNA end resection in eukaryotes

Abstract: The repair of DNA double-strand breaks (DSBs) by homologous recombination (HR) is initiated by nucleolytic degradation of the 5′ terminated strands in a process termed end resection. End resection generates 3′ single-stranded DNA tails, substrates for Rad51 to catalyze homologous pairing and exchange of DNA strands, and for activation of the DNA damage checkpoint. The commonly accepted view is that end resection occurs by a two-step mechanism. In the first step, Sae2/CtIP activates the Mre11-Rad50-Xrs2/Nbs1 (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
410
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(421 citation statements)
references
References 202 publications
(360 reference statements)
10
410
0
1
Order By: Relevance
“…Previously we demonstrated that BIR is strongly stimulated in cells under replication stress, and that many of these BIR events are initiated by breaks at FS2 . BIR events can initiate centromereproximal to the original break location due to extensive 59 to 39 end resection at DNA breaks to expose ssDNA (Chung et al 2010;Symington 2016).Both the extensive lengths and high abundance of bidirectional noncrossover tracts we observed can be explained if these tracts result not from canonical DSBR but from dBIR. The dBIR mechanism is also a better fit for our experimental system in which replication stress is likely to result in replication fork 124 S. A. Chumki et al…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Previously we demonstrated that BIR is strongly stimulated in cells under replication stress, and that many of these BIR events are initiated by breaks at FS2 . BIR events can initiate centromereproximal to the original break location due to extensive 59 to 39 end resection at DNA breaks to expose ssDNA (Chung et al 2010;Symington 2016).Both the extensive lengths and high abundance of bidirectional noncrossover tracts we observed can be explained if these tracts result not from canonical DSBR but from dBIR. The dBIR mechanism is also a better fit for our experimental system in which replication stress is likely to result in replication fork 124 S. A. Chumki et al…”
mentioning
confidence: 72%
“…Previously we demonstrated that BIR is strongly stimulated in cells under replication stress, and that many of these BIR events are initiated by breaks at FS2 . BIR events can initiate centromereproximal to the original break location due to extensive 59 to 39 end resection at DNA breaks to expose ssDNA (Chung et al 2010;Symington 2016).…”
Section: Types Of Mitotic Loh Stimulated By Instability At Fragile Simentioning
confidence: 99%
See 1 more Smart Citation
“…This initial binding helps recruit the NHEJ ligase, Lig4 which ligates DSB extremities even in the absence of significant homology. If not ligated by NHEJ, DSB is processed to generate 3′ single strand overhangs by partially redundant nucleases, which include Mre11/Sae2, Dna2 and Exo1 (Mimitou and Symington 2008;Cejka 2015;Symington 2016). The resulting 3′ss overhangs generated by the concerted action of MRX/Sae2, Exo1 and Sgs1/Dna2 proteins are rapidly stabilized by RPA.…”
Section: Introductionmentioning
confidence: 99%
“…DNA-PK promotes the ligation of two DNA ends by ligase IV, aided by the accessory factors XLF, XRCC4, and APLF, and in some cases aided by limited end processing (1,2). The recognition and repair of DNA breaks by the end-joining machinery is generally considered to be the first and rapid phase of DNA repair, occurring within ~30 minutes of DNA damage, while homologous recombination is specific to the S and G 2 phases of the cell cycle and occurs over a longer time frame (3,4). DNA-PK is present at micromolar concentrations in cells (5) and binds DNA ends in all cell cycle phases, even during S phase at single-ended breaks (6).…”
Section: Main Textmentioning
confidence: 99%